2019
DOI: 10.1111/bjd.18411
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation study of a melanoma risk prediction model incorporating clinically assessed naevi and solar lentigines

Abstract: Background Melanoma risk prediction models could be useful for matching preventive interventions to patients' risk.Objectives To develop and validate a model for incident first-primary cutaneous melanoma using clinically assessed risk factors. Methods We used unconditional logistic regression with backward selection from the Australian Melanoma Family Study (461 cases and 329 controls) in which age, sex and city of recruitment were kept in each step, and we externally validated it using the Leeds Melanoma Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…We included 42 studies in our TRIPOD rating. Forty studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were adopted from the systematic review about risk prediction models for melanoma published in 2020, whereas the remaining two studies [ 60 , 61 ] arose from the updated literature search. Details on the information extracted from the studies are summarized in Table A1 .…”
Section: Resultsmentioning
confidence: 99%
“…We included 42 studies in our TRIPOD rating. Forty studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were adopted from the systematic review about risk prediction models for melanoma published in 2020, whereas the remaining two studies [ 60 , 61 ] arose from the updated literature search. Details on the information extracted from the studies are summarized in Table A1 .…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, 24 of the 26 studies 39,40] from the two systematic reviews [13,15] were included in our analysis. Eight further studies were identified via forward snowballing [46,[49][50][51][52][53][54][55], while eight studies were found in PubMed [45,[56][57][58][59][60][61][62]. Therefore, we included 40 studies in our analysis (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Vuong et al . found strong discrimination in the initial test of the model [area under the curve (AUC) = 0·79] as well as in the external validation (AUC = 0·73) . The authors suggest that clinical assessment of whole‐body naevi and solar lentigines improved discrimination between individuals with and without melanoma as naevi were the most predictive risk factor.…”
mentioning
confidence: 98%
“…In this issue of the BJD, Vuong et al . describe a prediction model they developed for incident first‐primary cutaneous melanoma using the Australian Melanoma Family Study.…”
mentioning
confidence: 99%
See 1 more Smart Citation